Mother's Behavior: Infant and Young Children Feeding In Stunted Children - Apriyani Puji Hastuti; Dion Kunto Adi Patria; Novanda Ramadhani Nugraha (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Infant and Young Children Feeding (IYCF) are possible efforts​ used in prevention and reduction of stunting. Many children are deprived nutrition because food given too fast and inaccuracy responsive feeding. Level knowledge previous mother​ No know wrong way to be the right way appropriate. The aim of the study was mother knowledge about infant and young children feeding. For measure level of mother knowledge about infant and young children feeding and responsive feeding in toddlers and stunted children​ at the Public Health Center Sumbermanjing Kulon and Pagak in Malang Regency. Desain of this study used descriptive survey with a total of 60 respondents selected use total sampling technique. Data is collected through questionnaire that includes aspect knowledge mother, preparation and processing food, complementary feeding, and responsive feeding. Result of this study show that mother knowledge about infant and young children feeding in category good knowledge (67%), and less knowledge (33%). Based on every indicator from mother behavior show that preparation and processing food in category good (86%), complementary feeding in category good (100%), as well practice giving responsive feeding (80%). However, some mother is also lacking in responsive feeding (20%). Although level knowledge from Mother Enough high , related with knowledge mother who became source main that is support family too. This matter show necessity intervention that is not only focus on education and exposure but also on level I want to know, mother For increase knowledge Mother to giving eating in toddlers and children For in the future For prevent the occurrence of stunting.